Uncertainty in subject matter education—Constitutive element and fruitful instructional strategy? - Bähr, Ingrid; Bonnet, Andreas; Bracker da Ponte, Elisabeth; Gebhard, Ulrich; Krieger, Claus; Lübke, Britta; Sting, Wolfgang (Zeitschrift für Bildungsforschung (Internet), 2024)
Uncertainty, which is an essential element of life in globalised, mobile and digitalised post-modern societies, challenges educational institutions. Students must be empowered to deal with such uncertainty to support developing a sense of critical consciousness and agency. Drawing on the discourse of uncertainty in educational science, this qualitative secondary analysis (QSA) refers to two studies that focused on instructional ‘uncertainty-friendly’ settings in four different school subjects (biology, drama and physical education in one study and English as a foreign language in the other) to address the research question: What are students’ responses to didactically staged confrontations with disciplinary uncertainty in different subjects? In the analysed studies, the researchers established uncertainty-friendly settings as an instructional tool to foster deep learning and cognitive flexibility in K–12 students. This QSA compares students’ reactions to these settings. The findings suggest a cross-curricular pattern of student responses: In all subjects, students initially showed unspecific responses , all of which acknowledged uncertainty. In addition, students showed specific responses (i.e. the modes of juxtaposition, exploration and rejection ) as active interactions with the uncertainty of the settings. The results can further the development of uncertainty-friendly classrooms and reflection on their limitations.